Les basiliques à coupole de Dalmatie (Xe-XIe s.) : leur juste place dans la diffusion d’un type architectural de Byzance à l’Occident - Caillet, Jean-Pierre (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić’s 70th birthday, 2020)
The attention has already been drawn to the fact that around the year 1000, some Catalan and North- Italian churches with cupola possibly inherited their configuration from previous Byzantine models; on the other hand, the significance of Byzantine influence on several Dalmatian churches has not been ignored either. The present paper turns again to this topic, first focusing the interest on other antecedents in Southern Italy and Greece, then on Dalmatian key monuments of the 10th-11th centuries (i.e., the ones at the very beginning of an important regional diffusion), with particular distinction of their variants.It should also be added that the limited, but not absent impact of the proto-Romanesque, in some of these examples at least, has been taken into account as well. But historical background, as much in Southern Italy as in Dalmatia, can explain the prevalent connections with Byzantine monuments. And finally, taking into account the anteriority of the earliest Dalmatian attestations, regarding what was to occur in Catalonia especially, the Dalmatian achievements might have played a decisive role in the diffusion of such an architectural type from Eastern towards Western Mediterranean world.